ALLOYING OF CUPOLA CAST IRON WITH COPPER DUE TO APPLICATION OF COPPERBEARING WASTE - O. S. Komarov; V. I. Volosatikov; I. B. Provorova; N. B. Yurov; T. N. Meldzyuk (Литьë и металлургия, 2013)
The possibility of fortification of the cast iron smelted in cupola due to alloying it with copper of copper-bearing wastes is studied.